2002
DOI: 10.1046/j.1365-2702.2002.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

The transition of adolescents with diabetes from the children's health care service into the adult health care service: a review of the literature

Abstract: Adolescents with diabetes have unique health needs, which impact upon their transition from children's health care services into adult health care services. These health needs result from the precarious period in their lives, when they have to cope with the stresses of being a maturing person. This coincides with their move from the children's into the adult health care service. Whilst coping with these pressures they must also keep their diabetes under control. The impact of emotional and physical demands upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 37 publications
3
75
1
3
Order By: Relevance
“…There can also be issues of coming to terms with their own HIV status, secrecy and guilt among other family members, and dealing with HIV infection in the context of the adolescent transitional stage of development 11, 12. Once ART has been started, studies have found lower rates of viral suppression in young people with perinatal HIV infection compared with adults 13, which are probably attributable to adherence issues and poor clinic attendance rather than drug efficacy, both common problems among young adults living with other chronic diseases 1, 14, 15, 16. Findings from this study support the benefit of earlier age at diagnosis where possible, and initiation of ART prior to the adolescent period, which will probably also favour improved immunological health 17.…”
Section: Discussionmentioning
confidence: 99%
“…There can also be issues of coming to terms with their own HIV status, secrecy and guilt among other family members, and dealing with HIV infection in the context of the adolescent transitional stage of development 11, 12. Once ART has been started, studies have found lower rates of viral suppression in young people with perinatal HIV infection compared with adults 13, which are probably attributable to adherence issues and poor clinic attendance rather than drug efficacy, both common problems among young adults living with other chronic diseases 1, 14, 15, 16. Findings from this study support the benefit of earlier age at diagnosis where possible, and initiation of ART prior to the adolescent period, which will probably also favour improved immunological health 17.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the published literature on transition to adult care has focused on identifying the barriers facing this population as they proceed through this period [7,8,9,10,11]. The main barriers noted relate to patients, parents, organizations, environment, and care providers [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective care needs to encompass the various psychological, social and educational factors. To facilitate the process of transition, many pediatricians and diabetologists have concluded that transition clinics, run by multidisciplinary teams, are effective [12,13,14,15,16,17]. So far, however, little is known about the impact of transition clinics on metabolic and psychological outcomes [18, 19].…”
Section: Introductionmentioning
confidence: 99%